2020
DOI: 10.1093/nar/gkaa816
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 counteracts premature aging via m6A-dependent stabilization of MIS12 mRNA

Abstract: N6-Methyladenosine (m6A) messenger RNA methylation is a well-known epitranscriptional regulatory mechanism affecting central biological processes, but its function in human cellular senescence remains uninvestigated. Here, we found that levels of both m6A RNA methylation and the methyltransferase METTL3 were reduced in prematurely senescent human mesenchymal stem cell (hMSC) models of progeroid syndromes. Transcriptional profiling of m6A modifications further identified MIS12, for which m6A modifications were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 85 publications
4
105
0
Order By: Relevance
“…METTL3 knockdown and m 6 A depletion could limit self-renewal and promote cell differentiation in epiblast stem cells while improving pluripotency, block regeneration in embryonic stem cells [ 13 , 26 , 34 ]. A recent study suggested METTL3 knockout accelerated mesenchymal stem cell senescence by modulating m 6 A modification of MIS12 which supported our data [ 35 ]. In our study, METTL3 inhibition in immature DPSCs promoted cell senescence and apoptosis which might further result in reduced regenerative potential in mature teeth.…”
Section: Discussionsupporting
confidence: 92%
“…METTL3 knockdown and m 6 A depletion could limit self-renewal and promote cell differentiation in epiblast stem cells while improving pluripotency, block regeneration in embryonic stem cells [ 13 , 26 , 34 ]. A recent study suggested METTL3 knockout accelerated mesenchymal stem cell senescence by modulating m 6 A modification of MIS12 which supported our data [ 35 ]. In our study, METTL3 inhibition in immature DPSCs promoted cell senescence and apoptosis which might further result in reduced regenerative potential in mature teeth.…”
Section: Discussionsupporting
confidence: 92%
“…Library preparation and sequencing were performed as previously reported ( 53 ). Briefly, total RNAs were extracted using TRIzol Reagent, genomic DNAs were removed using the DNA-free Kit and mRNAs were purified by Poly (A) enrichment.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have discussed the mechanism of m6A-promoted cell senescence ( Li Q. et al, 2017 ; Wu et al, 2020 ). The METTL3/METTL14-mediated m6A methylation can enhance p21 expression which is further promoted.…”
Section: Discussionmentioning
confidence: 99%
“…oxidative stress-induced cellular senescence ( Li Q. et al, 2017 ). Through interacting with Lamin A, METTL3/14 can be properly localized in the nuclear speckles to achieve the regulatory function ( Wu et al, 2020 ). Our study has deepened the current understanding of m6A modification in cell senescence.…”
Section: Discussionmentioning
confidence: 99%